Given the following:
[tex]\begin{gathered} f(n+1)=f(n)-2 \\ \text{where f(1)=10} \end{gathered}[/tex]To generate the sequence, we have:
[tex]\begin{gathered} \text{when n=1} \\ f(1+1)=f(1)-2 \\ f(2)=10-2=8 \end{gathered}[/tex][tex]\begin{gathered} \text{when n=2} \\ f(2+1)=f(2)-2 \\ f(3)=8-2=6 \end{gathered}[/tex][tex]\begin{gathered} \text{when n=3} \\ f(3+1)=f(3)-2_{} \\ f(4)=6-2=4 \end{gathered}[/tex][tex]\begin{gathered} \text{when n=4} \\ f(4+1)=f(4)-2 \\ f(5)=4-2=2 \end{gathered}[/tex]Hence, the correct option is Option D